Fiscal policy, unemployment insurance, and financial crises in a model of growth and distribution - Greg Hannsgen (Levy Economics Institute of Bard College, 2012)
Recently, some have wondered whether a fiscal stimulus plan could reduce the government's budget deficit. Many also worry that fiscal austerity plans will only bring higher deficits. Issues of this kind involve endogenous changes in tax revenues that occur when output, real wages, and other variables are affected by changes in policy. Few would disagree that various paradoxes of austerity or stimulus might be relevant, but such issues can be clarified a great deal with the help of a complete heterodox model.
Keywords: E12; E32; E62; J65; 330; Financial Crisis; Post-Keynesian Economics; Fiscal-policy Rule; Dynamical System; Markup Dynamics; Kalecki-Steindl Model of Effective Demand; Hyman Minsky; Automatic Stabilizers; Growth Cycles; Budget Deficit; Capacity-utilization Targeting Rule; Historical Time; Policy Regime Switches; Keynesian Kaleidics; Chartalism; Distributive Curve